The day-of-week (DOW) effect on liberalism-conservatism: Evidence from a large-scale online survey in China - Shengquan Ye; Justin Juk Man So; Ting Kin Ng; Mac Zewei Ma (Frontiers in Psychology, 2023)
IntroductionPast research has shown that psychological states tend to fluctuate across the days of a week, which is referred to as the day-of-week (DOW) effect. This study investigated the DOW effect on liberalism-conservatism among Chinese people by testing two competing hypotheses. According to the cognitive states hypothesis, it was predicted that liberalism would be high on Mondays but gradually decrease to Fridays due to the depletion of cognitive resources over the weekdays. In contrast, the affective states hypothesis predicted the opposite, considering the more positive affect brought by the approaching weekends. Both hypotheses predicted the level of liberalism would peak at weekends.MethodsData (n = 171,830) were collected via an online questionnaire, the Chinese Political Compass (CPC) survey, which includes 50 items to measure people’ liberalism-conservatism in three domains (i.e., political, economic, and social).ResultsThe results showed the level of liberalism decreased gradually from Mondays until Wednesdays, rebounded from Wednesdays to Fridays, and peaked at weekends.DiscussionThe V-shaped pattern suggested that the DOW fluctuation in liberalism-conservatism could derive from the synergy of both cognitive and affective processes, instead of either one alone. The findings have important implications for practice and policy-making, including the recent pilot scheme of 4-day workweek.